HUBUNGAN SIKAP IBU DENGAN KEJADIAN UNDERWEIGHT PADA BALITA DI WILAYAH KERJA PUSKESMAS COT SEUMEURENG - Muriza Rahmatul Husna; Sri Wahyuni Muhsin; Ravi Masitah; Cukri Rahma (Jurnal Biogenerasi, 2026)
Good nutritional status in toddlers is essential for child health and development. Nationally, the prevalence of underweight among children under five in Indonesia is 15.9%, consisting of 3.0% severely underweight and 12.9% underweight, while 84.1% of toddlers have normal nutritional status. At the provincial level, Aceh shows a higher prevalence of underweight at 22.6%, including 4.9% severely underweight, 17.7% underweight, and 77.4% with normal nutritional status. At the district level, data from the Aceh Barat Health Office in 2024 recorded 530 cases of underweight, with the highest distribution in the working areas of Cot Seumeureung Health Center (85 cases), Kuala Bhee Health Center (84 cases), and Johan Pahlawan Health Center (83 cases).This condition highlights the importance of the mother’s role, particularly maternal attitudes toward fulfilling toddlers’ nutritional needs. This study aimed to analyze the relationship between maternal attitudes and the incidence of underweight among toddlers in the working area of Cot Seumeureung Health Center. A quantitative cross-sectional design was used, involving 63 mothers of children aged 0–59 months from three villages through total sampling. Data were collected from November to December 2025 using questionnaires, interviews, and anthropometric measurements based on WHO weight-for-age (WFA) z-score standards, and analyzed using the chi-square test (α = 0.05). The results showed that most mothers had positive attitudes toward toddler nutrition, and there was a significant relationship between maternal attitudes and the incidence of underweight (p = 0.040). In conclusion, maternal attitudes play an important role in determining toddlers’ nutritional status; therefore, underweight prevention efforts should focus on fostering positive attitudes, appropriate feeding practices, and strengthening continuous nutrition education and assistance through integrated health posts (posyandu) and health workers.